(untitled) (Communications in Mathematical Research, 2020)
While the spread of COVID-19 in China is under control, the pandemic is developing rapidly around the world. Due to the normal migration of population, China is facing the high risk from imported cases. The potential specific medicine and vaccine are still in the process of clinical trials. Currently, controlling the impact of imported cases is the key to prevent new outbreak of COVID-19 in China. In this paper, we propose two impulsive systems to describe the impact of multilateral imported cases of COVID-19. Based on the published data, we simulate and analyze the epidemic trends under different control strategies. In particular, we compare four different scenarios and show the corresponding medical burden. The results can be useful in designing appropriate control strategy for imported cases in practice.